Studi Kaderisasi Terhadap Partai Amanat Nasional (PAN): Problematika Calon Legislatif Artis - Muhammad Irfan Dhiaulhaq AR (Fakultas Hukum Universitas Islam Indonesia, 2023)
The participation of political parties in elections often creates its own container. Political parties function as a place where public interests congregate, articulate them into policies and build structures for individuals to participate in politics. This makes the essence of the election heats up. As Indonesia prepares for the 2024 elections, political parties are competing to create an effective regeneration system to produce quality candidates and improve the party's image. However, the focus on nominating high-profile and popular candidates, including celebrities, has marginalized many party members, hindering their chances of becoming future leaders. This paper aims to explore the challenges faced in developing party elite cadres in the National Mandate Party (PAN) and propose comprehensive solutions to strengthen cadres and regain public trust in the party. The research methodology used is normative legal research, using a descriptive analytic approach to analyze problems and propose solutions based on primary and secondary legal sources. The findings and discussion highlight the need for an effective recruitment mechanism, strengthen the party's education programs, and promote the importance of selecting candidates on the basis of quality and competence rather than popularity. By overcoming these problems, PAN can strengthen its cadres and rebuild public trust, contributing to a stronger party with competent leaders who represent the aspirations of the people.